INTERIOR DESIGN OF A PUBLIC LECTURE HALL AS AN EDUCATIONAL COMPONENT OF THE CREATIVE ENVIRONMENT IN A MODERN CITY - SHMELIOVA О. Ye.; SAFRONOVA О. О.; TRONCIU, S. P.; POLIAKOVA, O.V.; HAVRYLIEVA, T. V. (Art and Design, 2022)
The purpose of the study is to identify the design aspects of a public lecture hall as an educational component of the socio-cultural environment in a modern city. Methodology. The study is based on structural-systemic, historical-cultural, comparative, logical methods, as well as art history methods. The core base of the study is scientific articles of Ukrainian and foreign authors, analogous projects of public lectures in Ukraine and abroad. Results. The influence of public lecture halls on the formation of cultural and social interests of the inhabitants of the modern metropolis is determined. The types of lecture halls are analyzed as part of socio-cultural educational spaces which are a tool for forming a creative society. The classification of public lecture halls according to the main features is developed. The Ukrainian and foreign experience of designing public lecture halls is analyzed, and the peculiarities of their interior design are generalized. Scientific novelty. The concept of the lecture hall as a component of the creative urban space, which has an impact on the formation of the socio-cultural environment of the city and on improving knowledge of the modern population, is clarified. The Ukrainian and foreign experience of creating educational public lecture halls is analyzed and systematized. Practical significance. Research on the socio-cultural role of modern public lecture halls as a type of urban creative environment, as well as the basic principles of design of its premises, will be useful for modern design and promotion of educational spaces.